Rv1288, a Two Domain, Cell Wall Anchored, Nutrient Stress Inducible Carboxyl-Esterase of Mycobacterium tuberculosis, Modulates Cell Wall Lipid - Maan, Pratibha; Kumar, Arbind; Kaur, Jashandeep; Kaur, Jagdeep (Frontiers in Cellular and Infection Microbiology, 2018)
Rv1288, a conserved hypothetical protein of M. tuberculosis (M.tb), was recently characterized as two-domain esterase enzyme by in silico study. In the present study, Rv1288 and its domains (Est and Lyt) were cloned individually from M.tb into E. coli for expression and purification. The purified rRv1288 and rEst proteins exhibited lipolytic activity with medium chain length esters as optimum substrates, while Lyt domain did not show enzymatic activity. However, presence of Lyt domain resulted in enhanced rate of protein aggregation at higher temperature. Both rRv1288 and rEst followed the similar patterns of substrate specificity, temperature and pH activity. Site directed mutagenesis confirmed the Ser-294, Asp-391 and His-425 as catalytic site residues. Rv1288 was found to be present in cell wall fraction of M.tb H37Ra. Peptidoglycan binding activity of Rv1288 and its domains demonstrated that the Lyt domain is essential for anchoring protein to the cell wall. Expression of rv1288 was up regulated in M.tb under nutrient starved condition. Over expression of rv1288 in surrogate host M. smegmatis led to change in colony morphology, enhanced pellicle and aggregate formation that might be linked with the changed lipid composition of bacterial cell wall. Cell wall of M. smegmatis expressing rv1288 had higher amount of lipids, with a significant increase in trehalose dimycolate content. Rv1288 also leads to increase in drug resistance of M. smegmatis. Rv1288 also enhanced the intracellular survival of M. smegmatis in Raw264.7 cell line. Overall, this study suggested that Rv1288, a cell wall localized carboxyl hydrolase with mycolyl-transferase activity, modulated the cell wall lipids to favor the survival of bacteria under stress condition.